Tecnologías en línea populares para viajar: ¿cuáles utilizan los jóvenes universitarios para hacer turismo? - Castro Ricalde, Diana; Peñaloza Suárez, Laura; Tamayo Salcedo, Ana Leticia (Universidad de Costa Rica, 2018)
This paper aims to show the most popular technological tools online that allow the planning and realization of trips, also there is an identification of tools used by university students whose training as a tourism professional. There is the recognition of an issue in the educative scope which involve the lack of knowledge about the technology used by the students and there is considered the effects of these technological tools in the learning process. The theoretical framework approaches Technological Determinism and the methodology to analyses the data was mix method, including quantitative and qualitative techniques, this method allowed to recognize the way young students do online tourism, what kind of technologies they prefer and the conditions for traveling. The techniques to gather the information include a digital questionnaire in which 236 post-grade tourism students participate from all semesters at Autonomous Mexico State University. Moreover, 10 students from 2017A period participated in the focus group. The results show the tools that are used to communicate and look for information on line after of a trip, also it was found that the technologies make easier to customize of the displacements and aspects that the participants should know to make tourism and E-commerce. To conclude there is a need, in technological terms, in the university to approach technologies during the professional training and encourage E-Tourism